2017
DOI: 10.1515/mammalia-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

New record of feeding behavior by the porcupine Coendou spinosus (F. Cuvier, 1823) in high-altitude grassland of the Brazilian Atlantic Forest

Abstract: Abstractis a rodent from the Brazilian Atlantic Forest with a cryptic behavior that hinders collection of information regarding its ecology. On October 2014, we observed an individual of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
1
6
0
Order By: Relevance
“…Although recent studies have identified the occurrence of greyheaded tayra over 2,400 m of altitude in Peru (Rodríguez & Amanzo 2001), Costa Rica (Mooring et al 2011), Colombia (Ramírez-Mejía & Sánchez 2015 and Ecuador (Reyes-Puig et al 2015), all these records were obtained in forest formations in the Andes. Geise et al (2004) studied the elevational distribution pattern of non-volant mammals in the INP and identified that species richness was higher in montane forest, at 500-1,499 m of altitude, which is in agreement with studies showing that species richness can reach its maximum at mid-elevations (Heaney However, recent records revealed that some species of mammals, such as primates (Aximoff 2015, Aximoff & Vaz 2016, rodents (Abreu et al 2016) and bats (Martins 2011), are using higher areas than previously known in the INP. Other species of mammals have expanded their altitudinal range in Brazil (Oliveira et al 2003) and in other countries of South America (Shanee et al 2014).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Although recent studies have identified the occurrence of greyheaded tayra over 2,400 m of altitude in Peru (Rodríguez & Amanzo 2001), Costa Rica (Mooring et al 2011), Colombia (Ramírez-Mejía & Sánchez 2015 and Ecuador (Reyes-Puig et al 2015), all these records were obtained in forest formations in the Andes. Geise et al (2004) studied the elevational distribution pattern of non-volant mammals in the INP and identified that species richness was higher in montane forest, at 500-1,499 m of altitude, which is in agreement with studies showing that species richness can reach its maximum at mid-elevations (Heaney However, recent records revealed that some species of mammals, such as primates (Aximoff 2015, Aximoff & Vaz 2016, rodents (Abreu et al 2016) and bats (Martins 2011), are using higher areas than previously known in the INP. Other species of mammals have expanded their altitudinal range in Brazil (Oliveira et al 2003) and in other countries of South America (Shanee et al 2014).…”
supporting
confidence: 74%
“…Furthermore, Raboy et al (2013) suggest that food resources in high-altitude environments may be more abundant than previously thought. For example, according to Abreu et al (2016), the rodent Coendou spinosus was observed for the first time feeding on the flowers of vine species in the high-altitude grasslands of the INP, at the highest altitude ever recorded. These sites may also be used for dispersal of individuals seeking new groups, as has been suggested for primates (Aximoff & Vaz 2016).…”
mentioning
confidence: 99%
“…Primates and Erethizontidae rodents, such as S. libidinosus and C. prehensilis, respectively, are hardly affected by roadkill, mainly because they are arboreal animals and usually, spend more time on the ground in fragmented areas (Santos et al 2014, Abreu et al 2017, which is the case of our study area, and this could increase the chance of being roadkilled. Furthermore, C. prehensilis is herbivorous (Santos-Junior 1998) and S. libidinosus is omnivorous, and there are no records of scavenging habits for them (Vilela 2007, Freitas et al 2008, Sabbatini et al 2008.…”
Section: Coendou Prehensilismentioning
confidence: 86%
“…Knowledge about the natural history of species of the genus Coendou is still scarce, considering their cryptic habits, as nocturnal activity and long rest time in dense lianas or tree forks above the ground (Patton et al 2015, Abreu et al 2016. Coendou spinosus (F. Cuvier, 1823) occurs in humid tropical and subtropical of forests of Mata Atlântica of southeastern Brazil (from Espírito Santo State southward to Rio Grande do Sul State) and in similar contiguous habitats of northeastern Argentina, eastern Paraguay, and northern Uruguay (Patton et al 2015).…”
mentioning
confidence: 99%
“…Coendou spinosus (F. Cuvier, 1823) occurs in humid tropical and subtropical of forests of Mata Atlântica of southeastern Brazil (from Espírito Santo State southward to Rio Grande do Sul State) and in similar contiguous habitats of northeastern Argentina, eastern Paraguay, and northern Uruguay (Patton et al 2015). It is an arboreal rodent species capable of living in forest remnants with different conservation status and its feeding is reported as mainly composed of leaves (Passamani 2010) and flowers (Abreu et al 2016). Although the species feeds mainly on trees, there are reports of these mammals also feeding at ground level also (Abreu et al 2016).…”
mentioning
confidence: 99%